Pengaruh Persepsi Harga, Kualitas Produk, dan Pemasaran Media Sosial terhadap Minat Pembelian Produk Perawatan Kulit Pengguna Somethinc Generasi Z - Budiman, Budiman Abdulah; Alya, Alya Salsabila (Lembaga Teewan Journal Solutions, 2026)
The rapid growth of Indonesia's skincare industry has intensified competition among local brands, making it essential to understand the factors influencing Generation Z's purchase intention. This study examines the effects of price perception, product quality, and social media marketing on consumers' purchase intention toward Somethinc skincare products. A quantitative causal research design was employed, involving 122 Generation Z respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS software. The findings indicate that both price perception and product quality have a positive and significant effect on purchase intention. In contrast, social media marketing has a positive but insignificant effect. The coefficient of determination (R²) shows that these three variables jointly explain a substantial proportion of the variance in purchase intention. The results suggest that Generation Z places greater emphasis on reasonable pricing and product quality than on social media marketing activities when making purchase decisions. Therefore, skincare companies should maintain high product quality, offer prices that reflect the value perceived by consumers, and develop more credible and relevant social media marketing strategies to strengthen consumers' purchase intention.